2018
DOI: 10.1039/c8cc02250j
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of V2O5 as a low-cost rechargeable aqueous zinc ion battery cathode

Abstract: Rechargeable aqueous zinc ion batteries (ZIBs) are highly desirable for large-scale energy storage due to their advantages of safety and low-cost. Development of advanced cathodes for use in aqueous ZIBs is urgently needed. Herein, we report a low-cost rechargeable aqueous Zn-V2O5 cell with 3 M ZnSO4 electrolyte that demonstrates high zinc storage capability. We also investigated the effect of different types/concentrations of the aqueous electrolytes on the performance of the Zn-V2O5 cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
254
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 369 publications
(260 citation statements)
references
References 21 publications
6
254
0
Order By: Relevance
“…It should be pointed out that V 6 O 13 manifests a better, comprehensive electrochemical performance than most previously reported cathode materials in aqueous ZIBs (details in Table S1, Supporting Information), which represents a remarkable advance of aqueous ZIBs cathode materials. It can be observed that the V 6 O 13 material undergoes a rapid capacity decay in the initial stage, which is common in many previous reports . The phenomenon could mainly be attributed to two factors: for one thing, a little part of inserted Zn 2+ ions is located at the “dead Zn 2+ sites” and could not be extracted during the following charge process, resulting in a not‐completely reversible de‐intercalation process, which can be revealed in the high‐resolution X‐ray photoelectron spectroscopy (XPS) spectra in Figure b and Figure S3, Supporting Information, and energy dispersive spectrometer (EDS)‐mapping results in Figure S4, Supporting Information.…”
Section: Resultsmentioning
confidence: 51%
See 3 more Smart Citations
“…It should be pointed out that V 6 O 13 manifests a better, comprehensive electrochemical performance than most previously reported cathode materials in aqueous ZIBs (details in Table S1, Supporting Information), which represents a remarkable advance of aqueous ZIBs cathode materials. It can be observed that the V 6 O 13 material undergoes a rapid capacity decay in the initial stage, which is common in many previous reports . The phenomenon could mainly be attributed to two factors: for one thing, a little part of inserted Zn 2+ ions is located at the “dead Zn 2+ sites” and could not be extracted during the following charge process, resulting in a not‐completely reversible de‐intercalation process, which can be revealed in the high‐resolution X‐ray photoelectron spectroscopy (XPS) spectra in Figure b and Figure S3, Supporting Information, and energy dispersive spectrometer (EDS)‐mapping results in Figure S4, Supporting Information.…”
Section: Resultsmentioning
confidence: 51%
“…The cyclic voltammetry (CV) profiles in Figure a manifest several reduction peaks located at 0.55, 0.70, 0.86, and 0.95 V and the oxidation peaks at 0.64, 0.79, 1.01, and 1.09 V, demonstrating the multiple insertion/extraction process of Zn 2+ storage in V 6 O 13 . It can be observed that the first CV curve displays some variation when compared to the latter curves, which could be due to the activation process . The V 6 O 13 electrode demonstrates excellent rate performance (Figure b,c) up to 10 A g −1 .…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…[4][5][6][7] Therefore, the multivalent ions-based rechargeable batteries, such as Mg 2 + , Ca 2 + , Zn 2 + , and Al 3 + -based ones, have drawn decent scientific interests with the burning desire to explore alternative energy storage systems. [14] A few suitable ZIBs cathode materials to intercalate Zn 2 + can be classified into four categories: (1) Mn-based cathode materials (such as, α, β, γ-MnO 2 , Mn 2 O 3 ), [15][16][17][18] (2) V-based cathode materials (for example, M x V 2 O 5 , M x V 3 O 7 , and V 2 O 5 ), [4,12,19] (3) Prussian blue analogs-based cathodes: for example, MFe (CN) 6 (M = Na, Zn, Cu, Mn), [20][21][22][23] and (4) other cathode materials. [11][12][13] Meanwhile, it is of great importance to reduce the environment pollution and the cost by using aqueous electrolyte, but the high polarization, the narrow voltage range of Zn 2 + and the water splitting in the aqueous battery system limit many cathode materials for the intercalation of Zn 2 + .…”
Section: Introductionmentioning
confidence: 99%